Levels of peripheral Th17 cells and serum Th17-related cytokines in patients with colorectal cancer: a meta-analysis - Yan, Guoqiang; Liu, Tao; Yin, Libin; Kang, Zhenhua; Wang, Lei (Cellular and Molecular Biology, 2018)
Studies suggest that inflammation is involved in the colorectal cancer (CRC) pathology and symptoms. This study sought to quantitatively summarize the clinical cytokine data. Multiple reports have described the proportion of Th17 cells in peripheral blood and serum levels of Th17-related cytokines in patients with colorectal cancer (CRC). To clarify the status of Th17 cells and Th17-related cytokines in CRC patients, we did a meta-analysis of the results published previously to quantitatively assess the levels of peripheral Th17 cells and serum Th17-related cytokines in patients with CRC. We searched PubMed, Embase, web of Science, Cochrane Library and China National Knowledge Infrastructure (CNKI) systematically for studies reporting the proportion of Th17 cells and the serum levels of Th17-related cytokines (IL-17, IL-17A, IL-6, IL-22, IL-23) in CRC patients. Studies measuring the proportion of Th17 cells and the serum levels of Th17-related cytokines (IL-17, IL-17A, IL-6, IL-22, IL-23) in CRC and healthy control subjects were included. Mean (standard deviation) proportion of Th17 cells and cytokine concentrations for CRC and control subjects were extracted. We assessed pooled data by using a random-effects model. We identified 1276 studies, of which 24 studies were included in the final meta-analytical processes. The quality was reliable according to the Newcastle–Ottawa Quality Assessment Scale (Case Control Studies). Compared with control subjects, CRC patients had a higher proportion of Th17 cells [2.37%, (0.53, 2.21)]; an elevated levels of serum IL-17A 1.11 pg./ml, 95%CI (0.16-2.07); an elevated levels of serum IL-6 3.42 pg/ml, 95%CI (3.14-3.70); an elevated levels of serum IL-22 1.32 pg/ml, 95%CI (0.94-1.70); an elevated levels of serum IL-23 0.16pg/ml, 95%CI(1.94-5.39). After sensitivity analysis, an elevated level of serum IL-17 was showed. The data showed that the proportion of Th17 cells in PB and levels of serum IL-17, IL-17A, IL-6, IL-22, IL-23 increased among CRC patients compared to control subjects. This result demonstrated that Th17 cells and Th17-related cytokines may be involved in the pathogenic mechanisms of CRC.